A new species and new record of the Kamakidae (Crustacea: Amphipoda) from Korea - Jung, Tae Won; Yoon, Seong Myeong (Zootaxa, 2015)
Two species of the family Kamakidae collected from tidal flats on the southern west coast of Korea are reported, along with descriptions and illustrations. Kamaka excavata Ariyama, 2007 has the following unique character states on gnathopod 2 in the mature male: a wider coxa, a long and acute process of the propodus, and an excavation on inner-distal margin of dactylus. Although the new species, Kamaka rostra sp. nov. has gnathopod 2 similar to those of K. biwae Uéno, 1943, K. morinoi Ariyama, 2007, and K. appendiculata Ariyama et al., 2010, it can be easily distinguished by the plumose setae on the inner margin of the dactylus and by the spines on the inner lobe of the maxilliped in the mature male. In addition, this new species shows some particular characteristics among the species of Kamaka, such as the anterior cephalic lobe is not rounded but produced as a triangular shape, and uneven protuberances ranged along the inner-distal margin of the flagellum from peduncular article 5 to fourth proximal segment on antenna 2 in the mature male. This is the first report of the Kamakidae from Korean waters, and we also provide a key to worldwide Kamaka species.